The Rise of Female Professionals: Are Women Responding to Skill Demand? - Black, Sandra E; Juhn, Chinhui (American Economic Review, 2000)
For years, college-educated women were limited mainly to lower-paying, female-dominated professions such as teaching and nursing. Over the past several decades, however, there has been a remarkable increase in the percentage of college-educated women in higher-paying, “traditionally male” professional occupations. In 1967, the fraction of college-educated women working in these occupations was less than 20 percent. By 1997, this number had increased to almost 40 percent. This increase is particularly striking when compared to the slightly declining trend among college-educated men. What can explain this increase in female professionals? There are a number of possible explanations. One explanation is a demand shift favoring women over men in these highly skilled occupations. While the notion of a “gender-specific” demand shift is compelling in the case of high-school-graduate men and women, who work in very different industries and occupations, the story is much less convincing for the college-educated group. Collegeeducated men and women work in more similar occupations and are presumably closer substitutes for each other. To the extent that they are different, the available evidence suggests that this may have worked to the disadvantage of women (see Francine Blau and Lawrence Kahn, 1997). Another explanation, and the one we focus on in this paper, is that college-educated women have responded to the rise in overall skill demand, a phenomenon which has characterized the U.S. labor market during the 1980’s and perhaps even as early as the 1970’s. An important margin of response for these women may have been labor-market participation. In 1970, less than 60 percent of college-educated women were working. The economy-wide rise in skill demand may have attracted educated women not only from other occupations, but from nonparticipation as well. Since virtually all college educated men work, labor-market participation is less likely to be a factor for men. While we postulate that the overall increase in skill demand played an important role, we are also aware that this is not the only explanation. Within these high-wage professional occupations, women’s wages rose relative to male wages even as women increased their share. This suggests to us that declining discrimination (which both made it easier for women to enter these occupations and resulted in wage convergence vis a vis the male workers) or unobserved skill upgrading also may have played a role. In addition, the spread of more effective birthcontrol devices, Roe v. Wade, and no-fault divorce laws, just to name a few of the factors which changed marriage and fertility patterns of women, also most likely contributed to women’s willingness and ability to invest in “career jobs” (see Claudia Goldin and Lawrence Katz, 2000).